2011
DOI: 10.1016/j.ejphar.2010.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet-induced acute ischemia–reperfusion injury in mouse skeletal muscles: Involvement of superoxide

Abstract: Although arterial limb tourniquet is one of the first-line treatments to prevent exsanguinating hemorrhage in both civilian pre-hospital and battlefield casualty care, prolonged application of a limb tourniquet can lead to serious ischemia-reperfusion injury. However, the underlying pathomechanisms of tourniquet-induced ischemia-reperfusion injury are still poorly understood. Using a murine model of acute limb ischemia-reperfusion, we investigated if acute limb ischemia-reperfusion injury is mediated by supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 39 publications
5
60
0
3
Order By: Relevance
“…2, 3), and they suggest a reduction of levels of ROS generated by mitochondrial dysfunction and cellular injury and death in skeletal muscle after ischemia reperfusion. 21) Injection of DEX into crushed muscle resulted in a higher residual drug concentration compared to the other conditions. Therefore, control of local inflammation, indicated by reduced ROS and muscle MPO activity levels, showed beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3), and they suggest a reduction of levels of ROS generated by mitochondrial dysfunction and cellular injury and death in skeletal muscle after ischemia reperfusion. 21) Injection of DEX into crushed muscle resulted in a higher residual drug concentration compared to the other conditions. Therefore, control of local inflammation, indicated by reduced ROS and muscle MPO activity levels, showed beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…When oxygenated blood re-enters tissues during reperfusion, numerous reactive oxygen species (ROS) are generated that initiate injury beyond that caused by the ischemia [13,27]. For example, Zweier et al [28] reported that the peak for ROS generation in heart occurred rapidly in the first 10 seconds following reperfusion.…”
Section: Therapeutic Interventions Targeting I/r Injury Free Radical mentioning
confidence: 99%
“…During the pre-ischemic, ischemic, and initial 3 hours of reperfusion intervals, mice were placed on a heating pad to maintain body temperature at 37°C [14]. Tourniquet-induced I/R injury was identified by measuring blood flow to the gastrocnemius muscle as described previously [15, 16]. Blood flow dropped to approximately 2 % of baseline after placement of the tourniquet and remained at a steady level during the 3 hours of ischemia.…”
Section: Methodsmentioning
confidence: 99%